Breastfeeding Self Efficacy Dan Hubungannya Dengan Perilaku Ibu Menyusui - Isysi'aroh Isysi'aroh; Siti Rofiqoh (Pena Medika Jurnal Kesehatan, 2017)
High Self-efficacy is required to be able to comply with breastfeeding behavior. This study aim to identify the correlation of breastfeeding self-efficacy and breastfeeding behavior among mothers. Descriptive correlation design with cross-sectional approach was used in this study. The accidental sampling technique was used and gain 101 respondent. The results are the mean of breastfeeding self-efficacy among mothers is 54.4 (SD: 7.26), more than half of respondents have good breastfeeding behavior  63 (62.4%). The breastfeeing self-efficacy had a significant correlation with breastfeeding behavior (p: 0.38). As a recommendation, health worker give interventions to encourage breastfeeding self efficacy mothers to breastfeed properly are requisite.